Geriatric Psychiatry - Cunningham, Muriel (MD Conference Express, 2007)
This article provides an updated meta-analysis of memantine safety and efficacy for the treatment of moderate to severe Alzheimer's disease, as well as a discussion of the prevalence rates of depression and dementia, comparative safety and tolerability alzheimer's disease treatments, and the need for caregiver psychosocial training.